Changing the perception of premenstrual dysphoric disorder - An online-experiment using the Stereotype Content Model - Janda, C.; Asbrock, F.; Herget, M.; Kues, J. N.; Weise, Cornelia (Women & Health, 2019)
Women with Premenstrual Dysphoric Disorder (PMDD) are often faced with prejudices about the premenstrual phase. The aim of this study was to investigate whether providing information (psychoeducation) could improve study participants’ perception of a PMDD-patient and whether experimentally-induced prejudices about PMDD resulted in stigmatization. Two hundred sixteen students (50% female; aged 18–42 years) from Philipps University Marburg participated in January 2014. Participants were randomly assigned to one of two experimental groups (EG1, EG2) or to a control group (CG). EG1 read a text informing about PMDD. EG2 read a text with stereotypic PMDD-information. CG received a text with information unrelated to PMDD. Then, all participants watched a video of a woman reporting about her PMDD. Finally, participants appraised the woman on the cognitive dimensions warmth and competence as well as on PMDD-related attributes (depressive symptoms, emotional regulation). Participants of EG1 rated the woman as warmer (p < .001), more competent (p = .006), and with less depressive symptoms (p < .001) than the CG. The results by study group did not differ by gender. Stereotypic information did not differ significantly among the study groups. Psychoeducation can facilitate the understanding of PMDD-patients and should be integrated in future research on PMDD-treatments.
CRIS-Team Scopus Importer:2024-03-27
Keywords: Premenstrual Dysphoric Disorder (PMDD); premenstrual syndrome (PMS); Psychoeducation; Stereotype Content Model (SCM); Stigmatization